Common Purpose, Uncommon Results: A Literacy Collaboration for a Preschooler with Down Syndrome - Morris, Chelsea T.; Chidester, Rachel J. (Journal of the American Academy of Special Education Professionals, 2018)
This paper describes a single-case study that focused on an intervention to teach sight words to a preschool student with Down syndrome through a collaborative approach in which responsibility for design and implementation was shared by the child’s parents and her early childhood special education teacher. The intervention was consciously tailored in response to available research regarding the neurodevelopmental profile of children with Down syndrome. The aim of the intervention was focused on challenging deficit perspectives in special education and highlighting the importance of parent-teacher partnerships. Results indicated positive literacy outcomes, with the student retaining 14 of 22 (63%) sight words introduced as part of the intervention. Recommendations for future literacy interventions for children with Down syndrome and increased home-school collaboration are discussed.